2017
DOI: 10.11648/j.ejb.20170506.12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogenetic Study on <i>Pseudomonas stutzeri</i> Isolated from Currency Notes in Khartoum State, Sudan and Identified Via16s rRNA Gene Sequence Analysis

Abstract: Pseudomonas stutzeri is a valuable bacteria for understanding of the taxonomical and the phylogenetic relationships. The study of genetic relationships between organisms or genes is carried out by molecular phylogeny. We aim to study the relationships according to16S rRNA gene sequences between our samples and the closest strains from other countries over the world. To our knowledge, the phylogenetic studies between strains from Sudan with strains from other countries were not done before. A total of 140 curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Most of the bacterial species identified here have been implicated in many life threatening infections, which could pose a health risk particularly to immune compromised individuals in the community. In addition, to P. libanensis detected here for the first time from currency, the other GNB species have been already described with different levels of antibiotic resistance [3] , [8] , [9] , [13] , [14] . The obtained isolates could be from several sources depending on environmental conditions, age of money, handling or the poor sanitary condition and hygienic practices exercised by those manipulating currencies [2] , [3] .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Most of the bacterial species identified here have been implicated in many life threatening infections, which could pose a health risk particularly to immune compromised individuals in the community. In addition, to P. libanensis detected here for the first time from currency, the other GNB species have been already described with different levels of antibiotic resistance [3] , [8] , [9] , [13] , [14] . The obtained isolates could be from several sources depending on environmental conditions, age of money, handling or the poor sanitary condition and hygienic practices exercised by those manipulating currencies [2] , [3] .…”
Section: Discussionmentioning
confidence: 60%
“…However, after the outbreaks of some transmissible diseases, these reports have gained some serious consideration [11] , [12] and revealed that coins and paper currencies can serve as an ideal breeding for the multiplication of microorganisms [1] . In this study, we isolated different Gram negative bacteria species in agreement with several studies carried out on coin and paper currency collected from different sites including hospitals, public transport conductors and food vendors among different countries [1] , [2] , [3] , [9] , [13] . Most of the bacterial species identified here have been implicated in many life threatening infections, which could pose a health risk particularly to immune compromised individuals in the community.…”
Section: Discussionmentioning
confidence: 64%